The Effect of Cultural Intelligence and Creative Thinking on the Practical Technical Capabilities of Trabzon University Physical Education Students - Aydin, Elif (Asian Journal of Education and Training, 2019)
The purpose of this research was to investigate the effect of cultural intelligence and creative thinking on the practical technical capabilities of Trabzon University Physical Education Students. In order to measure the cultural intelligence, creative thinking and technical capabilities in sport, the Standard questionnaires of Early and Ang (2003), Torrance (2000) and Behringer et al. (2011) were used respectively. Cronbach’s alpha coefficient for the cultural intelligence, creative thinking and technical capability questionnaires were 0.79, 0.8, and 0.85, respectively. Questionnaires were distributed to 120 students, (40 for football, 40 for volleyball and 40 for badminton classes). The findings showed that cultural intelligence and creative thinking have a significant positive effect on the technical capabilities of Trabzon University Physical Education students in all three football lessons (foot technical capability), volleyball and badminton (hand technical capability). Also, cultural intelligence and creative thinking have a significant positive effect on the technical capabilities of football classes (foot technical capability). Cultural intelligence and creative thinking have a significant positive effect on the technical capabilities of students in volleyball classes (hand technical abilities). Cultural intelligence and creative thinking have a significant positive effect on the technical capabilities of badminton classes (hand technical ability). Finally, it can be said that cultural intelligence and creative thinking have a significant positive effect on the practical technical capabilities of physical education students of Trabzon University participating in practical lessons (football, volleyball and badminton) both simultaneously and separately in each classroom.